Model for Determining the Absorption Capacity of SMES in the Manufacturing Sector - Patricia Lagunes; Alberto Soto; Sofia Zuñiga; Juan Carlos Pérez (European Scientific Journal, ESJ, 2016)
This research aims at creating a model to determine the level of absorptive capacity in SMEs in the manufacturing sector through four dimensions (investment in R&D, number of patents, company structure, staff training); some authors propose measuring these or other variables separately, but based on the reviewed literature, the proposed model includes dimensions comprehensively identified as the most relevant, and the variables that allow a more accurate measurement absorptive capacity. It is important to underline that for the last ten years the research on this subject is being conducted mainly in countries of Asia.